Biopolymer-Based Nanogel Approach in Drug Delivery: Basic Concept and Current Developments - Altuntas, Ebru; Ozkan, Burcu; Gungor, Sevgi; Ozsoy, Yildiz (MDPI, 2023)
Due to their increased surface area, extent of swelling and active substance-loading capacity and flexibility, nanogels made from natural and synthetic polymers have gained significant interest in scientific and industrial areas. In particular, the customized design and implementation of nontoxic, biocompatible, and biodegradable micro/nano carriers makes their usage very feasible for a range of biomedical applications, including drug delivery, tissue engineering, and bioimaging. The design and application methodologies of nanogels are outlined in this review. Additionally, the most recent advancements in nanogel biomedical applications are discussed, with particular emphasis on applications for the delivery of drugs and biomolecules.
Keywords: biopolymers; nanogels; drug delivery; polysaccharide-based nanogels; protein-based nanogels; nanotechnology; SELF-ASSEMBLED NANOGEL; HYALURONIC-ACID; INTRACELLULAR DELIVERY; IN-VITRO; HYDROGEL NANOPARTICLES; CHITOSAN NANOPARTICLES; CHONDROITIN SULFATE; CROSS-LINKING; BIOMEDICAL APPLICATIONS; RESPONSIVE HYDROGELS; Pharmacology & Pharmacy